GAMBARAN PENGGUNAAN OBAT GASTRITIS PADA PASIEN RAWAT JALAN DI SALAH SATU RUMAH SAKIT DI PROVINSI RIAU - Nofriyanti Nofriyanti (Jurnal Penelitian Farmasi Indonesia, 2014)
Indonesia ranks fourth with the highest number of patients with gastritis after USA, England and Banglasdesh which totaled to 430 million people.Gastritis become one of the top ten most prevalent disease in outpatient in Indonesia which totaled to 30.154 cases (4,9%). The purposes of this studyto provide an overview of the usage of gastritis drugs quantitatively on outpatient at Departement of Internal Disease at one hospital in RiauProvince, according the proportions of gender, age range, type of gastritis, patent or generic, classes of drugs, type of gastritis drug and combinationsand interactions among the gastritis drug. The type of this study is observational with descriptive method using retrospective data. The selected data isgastritis patient medical record outpatient. The population of this study are the gastritis patient who outpatient at Departement of Internal Disease atone hospital in Riau Province totaled to 124 patients. The highest proportion based on gender totaled 67 persons (54,03%) are women, based on agerange totaled 99 persons (79,84%) are adult (18-55 years), based on type of gastritis totaled 48 cases (38,71%) are limfositic gastritis, based on patentand generic totaled 173 items ( 62,91%) are generics, based on classes of the drug totaled 115 items (41,82%) are proton pump inhibitor, based ontype drug of gastritis totaled90 items (32,73%) are Dexanta [A l(OH)3, Mg(OH)2, DMPS] and Lansoprazol, based on combinations and interactionsamong the gastritis drug totaled 65 items (30,66%) are combination of [Al(OH)3, Mg(OH)2, DMPS] and Lansoprazol.